2014
DOI: 10.1371/journal.pone.0085299
|View full text |Cite
|
Sign up to set email alerts
|

Fitting Characteristics of N95 Filtering-Facepiece Respirators Used Widely in China

Abstract: BackgroundMillions of people rely on N95 filtering facepiece respirators to reduce the risk of airborne particles and prevent them from respiratory infections. However, there are no respirator fit testing and training regulations in China. Meanwhile, no study has been conducted to investigate the fit of various respirators. The objective of this study was to investigate whether people obtained adequate fit when wearing N95 filtering facepiece respirators (FFRs) used widely in China.MethodsFifty adult participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 19 publications
(28 reference statements)
2
39
0
1
Order By: Relevance
“…This is unfortunate because studies have shown that the leakage around the mask, not through the medium, is the main determinant of total mask efficiency 18 . Poor fit can reduce an N95 mask from 95% to below 60% efficiency, which is below that of some masks made from commercial fabric 19,20 . In contrast, our testing setup uses a head model, upon which the mask is "worn", and is remarkably quick and easy to seal completely against the plastic film wrapped around the head model.…”
Section: Comparison With Other Methods and Facilitiesmentioning
confidence: 87%
“…This is unfortunate because studies have shown that the leakage around the mask, not through the medium, is the main determinant of total mask efficiency 18 . Poor fit can reduce an N95 mask from 95% to below 60% efficiency, which is below that of some masks made from commercial fabric 19,20 . In contrast, our testing setup uses a head model, upon which the mask is "worn", and is remarkably quick and easy to seal completely against the plastic film wrapped around the head model.…”
Section: Comparison With Other Methods and Facilitiesmentioning
confidence: 87%
“… 32 However, most of the respirators sold in China are designed according to specifications set by a panel of the US Los Alamos National Laboratory, which are based on facial features more typical of adults in Western countries. 33 Compared with the Western population, Asian populations have higher failure rates in fit testing for respirators of the same size. 34 In our study, although the use of N95 respirators among HCWs was better than that reported in previous studies, 10 12 13 only 50% of designated hospitals conducted fit-testing for respirators.…”
Section: Discussionmentioning
confidence: 99%
“…The fit of widely used N95 filtering facepiece respirators in China are poor because respirator manufacturers currently design their respirators in accordance with Los Alamos Laboratory fit test panels (Yu et al , 2014). The need for representative head-and-face shapes in China is great.…”
Section: Discussionmentioning
confidence: 99%